Influence of Organizational Culture on Cadets' Leadership Development in Transportation Management - Boy Laksmana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research investigates how organizational culture influences cadets' perceptions of empowerment training and shapes their leadership styles within the transportation management sector in Jakarta. Through qualitative interviews and quantitative surveys with cadets from diverse work environments—collaborative and hierarchical—the study explores the differential impacts of organizational culture on leadership development. Findings reveal that cadets in collaborative environments perceive empowerment training more positively, citing benefits such as teamwork, decision-making autonomy, and mentorship. These cadets tend to exhibit transformational leadership styles characterised by motivation, adaptability, and team empowerment. In contrast, cadets in hierarchical environments often adopt transactional leadership styles focused on task compliance and adherence to hierarchical structures. The study highlights the importance of tailored training programmes that accommodate diverse leadership styles and cultural contexts within transportation management education. Recommendations include integrating soft skills development, establishing mentorship programmes, and implementing continuous feedback mechanisms to enhance training effectiveness. By addressing these dynamics, educational institutions can better prepare cadets for leadership roles in dynamic professional environments, contributing to sectoral advancement and sustainability.